Focusing the mechanism of action to dissect the different treatments of respiratory allergy. (September 2015) - Incorvaia, Cristoforo; Moingeon, Philippe; Buttafava, Serena; Frati, Franco
Abstract : The treatment of respiratory allergy is based on several drugs with different mechanisms of action, which encompass an effect only on symptoms, limited factors of inflammation or the whole process of inflammation. Dissecting the different treatments by their mechanism of action is relevant for the management of allergic patients. Corticosteroids, administered as nasal sprays in rhinitis or by inhalation devices in asthma, and allergen immunotherapy (AIT) are the most effective treatments for respiratory allergy, achieving the control on inflammation by a number of cellular and molecular mechanisms. What distinguishes corticosteroids from AIT is the duration of clinical outcomes that ends with treatment withdrawal for the former but persists after stopping for AIT, due to its disease-modifying effect.